Transfusion-Transmitted Disorders 2023 with Special Attention to Bone Marrow Transplant Patients - Miklós Udvardy; Árpád Illés; Lajos Gergely; László Imre Pinczés; Ferenc Magyari; Zsófia Simon (Pathogens, 2023)
Transfusion medicine is traditionally a strong/fundamental part of clinical practice, saving hundreds of millions of lives. However, blood-borne or transmitted infections are a well-known and feared possibility, a risk we relentlessly mitigate. Pathogens are continuously and rather quickly changing, so during the last decade, many, sometimes exotic, new pathogens and diseases were recorded and analyzed, and some of them were proved to be transmitted with transfusions. Blood or blood component transfusions are carried out after cautious preparative screening and inactivation maneuvers, but in some instances, newly recognized agents might escape from standard screening and inactivation procedures. Here, we try to focus on some of these proven or potentially pathogenic transfusion-transmitted agents, especially in immunocompromised patients or bone marrow transplantation settings. These pathogens are sometimes new challenges for preparative procedures, and there is a need for more recent, occasionally advanced, screening and inactivation methods to recognize and eliminate the threat a new or well-known pathogen can pose. Pathogen transmission is probably even more critical in hemophiliacs or bone marrow transplant recipients, who receive plasma-derived factor preparations or blood component transfusions regularly and in large quantities, sometimes in severely immunosuppressed conditions. Moreover, it may not be emphasized enough that transfusions and plasma-derived product administrations are essential to medical care. Therefore, blood-borne transmission needs continued alertness and efforts to attain optimal benefits with minimized hazards.